Experimental study of the γP→π0π0p reaction with the crystal ball/taps detector system at the mainz microtron; Physical Review C; Vol. 85, № 6 - Kashevarov V. L.; Aguar-Bartolomé P.; Arends H. J.; Downie E. J.; Heid E.; Jahn O.; Ortega H.; Ostrick M.; Ott P.; Otte P. B.; Oussena B.; Schumann S.; et al. (2012, 2012)
Title screen